Reviews without a Purchase: Low Ratings, Loyal Customers, and Deception - Anderson, Eric T.; Simester, Duncan I. (Journal of Marketing Research, 2014)
The authors document that approximately 5% of product reviews on a large private label retailer's website are submitted by customers with no record of ever purchasing the product they are reviewing. These reviews are significantly more negative than other reviews. They are also less likely to contain expressions describing the fit or feel of the items and more likely to contain linguistic cues associated with deception. More than 12,000 of the firm's best customers have written reviews without confirmed transactions. On average, these customers have each made more than 150 purchases from the firm. This makes it unlikely that the reviews were written by the employees or agents of a competitor and suggests that deceptive reviews may not be limited to the strategic actions of firms. Instead, the phenomenon may be far more prevalent, extending to individual customers who have no financial incentive to influence product ratings.